PERLINDUNGAN HUKUM TERHADAP PEKERJA YANG MENERIMA UANG PESANGON TIDAK SESUAI UNDANG-UNDANG PADA PT. TRI DELMITA MANDIRI - Jihan Ramadhanty; Evi Deliana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Protection of workers is intended to guarantee basic rights of workers and ensure equality and treatment without discrimination on any basis to realize the welfare of workers and their families while still paying attention to developments in the progress of the business world and the interests of employers. Legislation related to the protection of workers Law Number 13 of 2003 concerning Manpower and the Implementing Regulations of the legislation in the manpower sector. Legal protection for workers is very necessary given the position of workers on the weak side. Law Number 13 of 2003 provides protection for workers which includes people who have not worked, people who are currently engaged in an employment relationship (workers / laborers), and people who have terminated their employment relationship. In the event of termination of employment, the entrepreneur is obliged to pay severance pay and / or service pay and compensation for entitlements that should have been received.From the results of the research and discussion, there are two main points that can be concluded. First, protection of workers is a legal imperative because the rights of workers who have been laid off are related to the needs of a person so that the government must protect these rights. All workers are protected by Law Number 13 of 2003 concerning Manpower, whether they are looking for work, who are currently working or who have already been laid off. The rights of laid-off workers have been described in Law Number 13 of 2003 concerning Manpower. Second, the inhibiting factor for companies to pay severance pay in accordance with applicable regulations is due to economic factors. The company experienced a decrease in income due to the emergence of competitors, which affected the company's income. Because the company has experienced a decline, the company is unable to pay severance pay in accordance with the provisions of Law Number 13 Year 2003 concerning Manpower.Keywords : Termination of Employment, Severance Pay.